Assessment of acute neurotoxicity of nitrogen-doped multilayer graphene nanoparticles and their capability to change Cd2+/Pb2+/Hg2+-induced injury in brain cortex nerve terminals - Dudarenko Marina; Krisanova Nataliya; Pozdnyakova Natalia; Pastukhov Artem; Pariiska Olena; Kurys Yaroslav; Sotnik Svitlana; Kolotilov Sergey V.; Koshechko Vyacheslav; Borisova Tatiana (Biotechnologia Acta, 2023)
Graphene materials are widely used in different technologies and certainly released into aquatic and air surroundings being environmental pollution components. Nitrogen‑doped graphene nanomaterials have great potential for application, in particular, in energy storage, as electrochemical sensors and waste water treatment.